How to improve brand image: The role of customer attitude, brand familiarity, brand awareness, and brand extension - Yazid, Yazid; Kawiryan, Helmidhia (Asian Management and Business Review, 2023)
This article is a publication of a research finding aimed to determine the influence of customer attitude, brand familiarity, brand awareness, and brand extension toward brand image (study case using toothpaste brand XYZ). Brand image is one of the key factors of brand managemrnt to stay survive in the future, to win the competition, to increase sales, and therefore increasing revenue. When consumers buy a products or services, they not just buy the products or services, they also buy what the brand stand for. It means that a brand should convey exactly what producers want it to say. Results of data analysis show that all of the independent variables contribute positive significant, both simultaneously and individually, influence on brand image, which, among the four independent variables, brand familiarity contributes the biggest positive significant influence on brand image. The implications of the findings will be discussed.